MECHANISMS OF IMMUNOLOGIC INJURY OF RAT PERITONEAL MAST CELLS : I. THE EFFECT OF PHOSPHONATE INHIBITORS ON THE HOMOCYTOTROPIC ANTIBODY-MEDIATED HISTAMINE RELEASE AND THE FIRST COMPONENT OF RAT COMPLEMENT - Becker, Elmer L. (The Rockefeller University Press, 1966)
The ability of a number of p-nitrophenylethyl, alkyl phenylalkyl, chloroalkyl, and aminoalkyl phosphonates to inhibit the homocytotropic antibody-mediated release of histamine from rat peritoneal mast cells has been tested. The effectiveness of these same phosphonates against the activated first component of rat complement (C'1a) has also been investigated. The rat mast cell esterase activated by the reaction of antigen and homocytotropic antibody resembles chymotrypsin in its reactivity with the phenylalkyl and chloroalkyl phosphonate, but is unlike this protease in its greater responsiveness to the 5-aminopentyl phosphonate relative to the pentyl phosphonate. The antigen-homocytotropic antibody-activated mast cell esterase and chymotrypsin, thus, appear to be similar, but different enzymes; i.e., they are parazymes (see reference 4, p. 501). There are distinct differences in the pattern of inhibition given by the phenylalkyl and aminoalkyl and alkyl phosphonates of the homocytotropic antibody-mediated histamine release from rat peritoneal mast cells and from guinea pig lung slices. On the basis of these differences it is concluded that the esterases activated by the combination of antigen and homocytotropic antibody on the mast cells of the two species are not the same. The arithmetic dose response curve found for the action of the phosphonates on the antigen-induced histamine release from rat peritoneal mast cells contrasted sharply with the logarithmic relationship found when these same inhibitors acted on the guinea pig lung system. This suggests that in addition to the antigen-antibody-activated esterases being unlike, the detailed mode of histamine release from the mast cells of the guinea pig lung differs from that of the mast cells of the rat peritoneum. Distinct and large differences were found in the pattern of inhibition of histamine release from rat peritoneal mast cells and of rat C'1a given by the phenylalkyl, and chloroalkyl and alkyl phosphonates implying that esterase activated by the combination of antigen with the sensitized rat peritoneal mast cells is not C'1a. Thus, the results with the peritoneal mast cells lead to the same conclusion as the previous work with guinea pig lung slices; i.e., the antigen-antibody-activated esterase involved in the homocytotropic antibody-mediated release of histamine is not part of the complement system.